Three Decades of Budget Deficit and Shock Responses: The Malaysia Case - Yew, Sze-Shin; Chan, Tze-Haw (Journal of Entrepreneurship, Business and Economics, 2019)
Malaysia has experienced budget deficits for the past three decades. The accumulated deficits and public debts have escalated, thus casted doubts on the capacity of fiscal expansion to endure economic growth. Yet, the limited empirical evidences are far from conclusive. This paper examines the Malaysian budget deficit-economic growth nexus during 1980-2018, with other macroeconomics variables (e.g. interest rate, inflation, exchange rate, domestic investment) taken into consideration. To capture the dynamic relationship, a set of comprehensive econometric procedures has been employed, including cointegration, Granger causality, error correction modelling, impulse response function and variance decomposition. Our analysis reveals that budget deficits contributed to economic growth and were bounded together with macroeconomic variables in both the long-run and short run with different magnitudes and shock adjustments. In brief, GDP is negatively linked to budget deficits, foreign exchange rate and interest rate, but positively linked with domestic investment and inflation. In addition, budget deficits exhibited bidirectional causality with domestic investment, and showed unidirectional causal effect on GDP. The finding would suggest that increases of budget deficits and domestic investment promotes economic productivity. Monetary expansion with lower interest rate and exchange rate appreciation would help to correct budget deficits but the impacts are minor, due to less-profound financial deepening. A balancing and well-coordinated public finance policy would help to sustain economic growth. Research paper  Keywords: Budget Deficit, Public Debts, Financial Crises, Macroeconomics variables, Sustainable Growth Reference to this paper should be made as follows: Yew, S., & Chan, T. (2019). Three Decades of Budget Deficit and Shock Responses: The Malaysia Case, Journal of Entrepreneurship, Business and Economics , 7 (2s), 144–178.